THE DIFFERENCE OF QUALITY OF LIFE AND COGNITIVE FUNCTION BETWEEN PATIENTS WITH AND WITHOUT AGE-RELATED MACULA DEGENERATION (AMD) - Kristianto, Bobby; Sukartini Djelantik, Anak Agung Ayu; Andayani, Ari; Putrawati Triningrat, Anak Agung Mas; Juliari, I Gusti Ayu Made; Widiana, I Gde Raka (Indonesian Vitreoretinal Society, 2021)
Introduction: To determine the difference in the quality of life and cognitive function in patients with and without AMD. Methods: This research is an observational analytic study, a prospective cross sectional study in the polyclinic of RSUP Sanglah, Denpasar. Result: Study samples’s total are 66 people selected by consecutive sampling with 33 people in the group with AMD, and 33 people in the group without AMD. The results of the study showed the average age of the group with AMD 68 years and the group without AMD 67 years old. Most of the male sex and residence in denpasar in both groups. Most AMD with the wet type by 60.6 %. On the measurement of quality of life, it showed decreasing in all subscale in the group with AMD compared to the group without AMD with total average 27.2 % and also decreasing in cognitive function measured by MMSE in the group of AMD compared to the group of non – AMD with 6.8%, even though the MMSE score of the groups are within normal limits. All these things stated significant differences (p<0.05) statistically. Conclusion: There are decreasing quality of life and cognitive function in AMD groupd compared to Non-AMD group which is needed more treatment and screening in the future.